THE INFLUENCE OF PRODUCT QUALITY AND PRICE ON CONSUMER PURCHASING DECISIONS FOR AIR DODOLA PRODUCTS IN MOROTAI ISLAND REGENCY - Natan, Nurdin; T. Asu, Iin Nirwanasari; Wangko, Lukman; Sibua, Nurhikmah; Yuliana, Yuliana (International Journal of Multidisciplinary Research and Literature, 2026)
This study aims to analyse the influence of product quality and price on consumer purchasing decisions regarding Air Dodola in Morotai Island Regency. The study used a quantitative approach by distributing questionnaires to 50 respondents who had purchased and consumed Dodola Water products. The data obtained were analysed using multiple linear regression through SPSS software version 29. The results showed that product quality partially had a positive and significant effect on purchasing decisions, with a t-value of 5.983 and a significance of 0.000. It indicates that consumers tend to make more purchases if they assess the product quality as good, including taste, packaging, cleanliness, and product safety. Furthermore, price also has a positive and significant effect on purchasing decisions, with a t-value of 8.345 and a significance of 0.000, indicating that consumers' perceptions of affordable prices commensurate with the product's benefits increase their tendency to buy. Simultaneously, product quality and price have a significant effect on purchasing decisions with an F-value of 35.327 and a significance level of 0.001. These findings confirm that the combination of high product quality and appropriate pricing is a major driver of consumer interest in purchasing Air Dodola in Morotai Island Regency, with strategic implications for product marketing management.